Handedness, time use and early childhood development - David W. Johnston; Manisha Shah; Michael A. Shields (Institute for the Study of Labor (IZA), 2007)
We test if there is a differential in early child development by handedness, using a comprehensive range of measures covering, learning, social, cognitive and language skills, evaluated by both interviewer conducted tests and teacher assessments. We find robust evidence that left-handed children do significantly worse in nearly all measures of development, with the relative disadvantage being larger for boys than girls. Importantly, these differentials cannot be explained by different socio-economic characteristics of the household, parental attitudes or investments in learning resources. In addition, using data from child time use diaries, we find evidence that lefthanded children spend significantly less time each day on educational activities than their righthanded peers, and significantly more time watching television. However, these behavioural differences explain less than 10% of the handedness child development differential. The results of this paper clearly show that handedness differentials are evident even in early childhood.
urn:nbn:de:101:1-20080402222
Keywords: 330; Kinder; Zeitbudgetforschung; Persönlichkeitspsychologie; Australien